‘In the Beginning’: Three Catholic Insights into Hinduism: Vasco Da Gama, Saint Francis Xavier and Roberto De Nobili - Didier, H. (The Downside review, 2023)
Before the landing of Vasco Da Gama and his seamen, India did not remain an isolated world: during the 4th century B.C., Alexander the Great reached the Indus. During the Middle Ages, Indian themes enjoyed a remarkable expansion in the West. In the mind of the Portuguese discoverers, the concept of an eastern Christianity created by Saint Thomas the Apostle was a deciding factor. Elsewhere, the Moslem abrahamised Hinduism: this was another source of confusion. The apostle of India, Saint Francis Xavier (1506-1552) belonged to the pre-Tridentine period: therefore, he demonised Hinduism. His meetings with the Brahmans were rather confrontational. But, with Roberto de Nobili (1577-1658) the Christian mission took an alternative path. We must take into account the struggle for indianising Christianity, conceived by Father De Nobili. Unfortunately, this enterprise evaded the key-problem of Hindu esotericism and metaphysical monism.